Westonci.ca is the ultimate Q&A platform, offering detailed and reliable answers from a knowledgeable community. Explore comprehensive solutions to your questions from knowledgeable professionals across various fields on our platform. Experience the ease of finding precise answers to your questions from a knowledgeable community of experts.
Sagot :
To solve for the roots of the quadratic equation [tex]\(x^2 + 3x - 6 = 0\)[/tex] using the Quadratic Formula, we start by identifying the coefficients in the given equation.
The standard form of a quadratic equation is:
[tex]\[ ax^2 + bx + c = 0 \][/tex]
In our equation, [tex]\(x^2 + 3x - 6 = 0\)[/tex], the coefficients are as follows:
- [tex]\(a = 1\)[/tex]
- [tex]\(b = 3\)[/tex]
- [tex]\(c = -6\)[/tex]
The Quadratic Formula is given by:
[tex]\[ x = \frac{-b \pm \sqrt{b^2 - 4ac}}{2a} \][/tex]
Let's break down the steps to solve for the roots:
1. Calculate the Discriminant:
The discriminant ([tex]\( \Delta \)[/tex]) is found using the formula:
[tex]\[ \Delta = b^2 - 4ac \][/tex]
Substituting the values of [tex]\(a\)[/tex], [tex]\(b\)[/tex], and [tex]\(c\)[/tex]:
[tex]\[ \Delta = 3^2 - 4 \cdot 1 \cdot (-6) = 9 + 24 = 33 \][/tex]
2. Check the Sign of the Discriminant:
Since the discriminant is positive ([tex]\( \Delta = 33 \)[/tex]), this indicates that there are two real and distinct roots.
3. Calculate the Roots:
Using the Quadratic Formula, we find the roots as follows:
[tex]\[ x_{1,2} = \frac{-b \pm \sqrt{\Delta}}{2a} \][/tex]
[tex]\[ x_{1,2} = \frac{-3 \pm \sqrt{33}}{2 \cdot 1} \][/tex]
Thus:
- The first root ([tex]\(x_1\)[/tex]) is:
[tex]\[ x_1 = \frac{-3 + \sqrt{33}}{2} \approx 1.3722813232690143 \][/tex]
- The second root ([tex]\(x_2\)[/tex]) is:
[tex]\[ x_2 = \frac{-3 - \sqrt{33}}{2} \approx -4.372281323269014 \][/tex]
Summarizing, the quadratic equation [tex]\(x^2 + 3x - 6 = 0\)[/tex] has the discriminant 33, and the roots are approximately 1.3722813232690143 and -4.372281323269014.
The standard form of a quadratic equation is:
[tex]\[ ax^2 + bx + c = 0 \][/tex]
In our equation, [tex]\(x^2 + 3x - 6 = 0\)[/tex], the coefficients are as follows:
- [tex]\(a = 1\)[/tex]
- [tex]\(b = 3\)[/tex]
- [tex]\(c = -6\)[/tex]
The Quadratic Formula is given by:
[tex]\[ x = \frac{-b \pm \sqrt{b^2 - 4ac}}{2a} \][/tex]
Let's break down the steps to solve for the roots:
1. Calculate the Discriminant:
The discriminant ([tex]\( \Delta \)[/tex]) is found using the formula:
[tex]\[ \Delta = b^2 - 4ac \][/tex]
Substituting the values of [tex]\(a\)[/tex], [tex]\(b\)[/tex], and [tex]\(c\)[/tex]:
[tex]\[ \Delta = 3^2 - 4 \cdot 1 \cdot (-6) = 9 + 24 = 33 \][/tex]
2. Check the Sign of the Discriminant:
Since the discriminant is positive ([tex]\( \Delta = 33 \)[/tex]), this indicates that there are two real and distinct roots.
3. Calculate the Roots:
Using the Quadratic Formula, we find the roots as follows:
[tex]\[ x_{1,2} = \frac{-b \pm \sqrt{\Delta}}{2a} \][/tex]
[tex]\[ x_{1,2} = \frac{-3 \pm \sqrt{33}}{2 \cdot 1} \][/tex]
Thus:
- The first root ([tex]\(x_1\)[/tex]) is:
[tex]\[ x_1 = \frac{-3 + \sqrt{33}}{2} \approx 1.3722813232690143 \][/tex]
- The second root ([tex]\(x_2\)[/tex]) is:
[tex]\[ x_2 = \frac{-3 - \sqrt{33}}{2} \approx -4.372281323269014 \][/tex]
Summarizing, the quadratic equation [tex]\(x^2 + 3x - 6 = 0\)[/tex] has the discriminant 33, and the roots are approximately 1.3722813232690143 and -4.372281323269014.
Thank you for your visit. We're dedicated to helping you find the information you need, whenever you need it. Thanks for using our service. We're always here to provide accurate and up-to-date answers to all your queries. Keep exploring Westonci.ca for more insightful answers to your questions. We're here to help.